Strengthening community health cadres’ capacity in household emergency first aid - Ajeng Purwanty (Bakti Nusantara Pengabdian Masyarakat Indonesia, 2026)
Background: Household emergencies are common events that require prompt and appropriate first-aid management to prevent complications and reduce the risk of delayed treatment. In many communities, health cadres play an important role as frontline community agents; however, limited knowledge and practical skills in first aid may weaken their preparedness to respond effectively to emergency situations at home. Objective: This community service program aimed to enhance the capacity of health cadres in providing first aid for household emergencies through an educational and simulation-based training approach. Methods: A promotive–preventive training design was implemented involving 50 community health cadres. The intervention consisted of interactive lectures, group discussions, practical demonstrations, case-based simulations of household emergencies, and mentoring sessions. Program evaluation focused on participant characteristics and changes in knowledge, practical skills, ability to recognize emergency conditions, basic resuscitation simulation skills, and overall preparedness before and after the training. Results: Most participants were aged 36–50 years (52.0%), female (76.0%), had a secondary education level (44.0%), had served as health cadres for 2–5 years (40.0%), and had never previously attended first-aid training (70.0%). After the intervention, marked improvements were observed across all competency indicators. The proportion of cadres with good first-aid knowledge increased from 32.0% to 84.0%; good minor wound management skills from 36.0% to 80.0%; ability to recognize emergency conditions from 40.0% to 86.0%; basic resuscitation simulation skills from 24.0% to 76.0%; and preparedness to manage household emergencies from 34.0% to 82.0%. Conclusion: Educational and simulation-based first-aid training effectively improved the knowledge, practical skills, and preparedness of community health cadres in responding to household emergencies. Strengthening cadre competency through continuous training, periodic monitoring, and multisectoral support is essential to sustain community readiness and improve family emergency response capacity.